Solid catalysts for conversion of furfural and its derivatives to alkanediols - Enjamuri, Nagasuresh; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2020)
Alkanediols with five and six carbon atoms (1,2- & 1,5-pentanediols and 1,2- & 1,6-hexanediols, respectively) are an important class of industrial chemicals having wide application. Their production from lignocellulosic biomass-derived furfural and its derivatives using solid catalysts is a sustainable and attractive approach. Several bifunctional catalysts with metal (for hydrogenation/hydrogenolysis) and acid/base (for ring opening) functionalities have been reported. Effective and selective conversion of furfurals to a desired diol is still a challenge. This review discusses the recent advances in catalyst development for pentane- and hexanediols. The reaction pathways, active sites, and possible reaction mechanisms over the solid catalysts are discussed. A comparative catalytic activity data of the known catalysts are reported.
Keywords: 5-hydroxymethylfurfural (HMF); Alkanediol; furfural (FAL); hexanediol; pentanediol; solid catalyst

Advances in catalytic conversion of lignocellulosic biomass to ethylene glycol - Enjamuri, Nagasuresh; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2024)
Ethylene glycol (EG) is an industrial chemical with multiple applications in polymers, anti-freeze agents, coolants, desiccants and de-icing fluids. It is prepared mainly from fossil feedstock resources. However, its manufacture from renewable sources like lignocellulosic biomass is attractive from the view points of carbon-neutrality and environmental benefits. A few industries have already ventured or committed to produce biomass-derived EG (bio-EG) on a pilot to demonstration scale. At present bio-EG is more expensive than the EG made from fossil resources. Advances are happening in developing more efficient and selective catalysts for the direct conversion of raw biomass and its hydrolysis products (cellulose and glucose) into bio-EG. This review presents the recent advances in catalysts for producing bio-EG.
Keywords: 2-diol; biomass to chemicals; ethane-1; Hydrogenolysis; Lignocellulose; Monoethylene glycol; solid catalyst